Gebyuran Bustaman: A Religious Tradition Before Ramadan in Semarang's Annual Tourism Event as Intangible Cultural Heritage - Zahrina Nabila Abidin; Choirul Anwar (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: The purpose of this study is to examine Gebyuran Bustaman in the context of religious tradition prior to Ramadan, with a focus on its transformation into an annual cultural tourism event in Semarang. Method: The present study employs a qualitative approach, which is to be achieved by means of the following: observation, interviews with youth organisers, and media documentation analysis (news portals, government social media, local websites). Result: The findings of the Gebyuran Bustaman ceremony have successfully preserved its sacred values amid efforts to promote tourism as part of the Semarang Event Calendar. This sacredness is continually upheld through a series of community ritual practices, such as grave visits, collective prayers for the departed, and the use of well water where Kyai Bustam purified himself at the climax of the event. Additionally, there are moral guidelines for participating tourists to avoid getting angry when hit by splashed water. This has led to varied framing in mass media coverage, shaping public perception within the spectrum between ritual and tourism. Contribution: This study makes a significant contribution to the existing literature on cultural tourism by shedding light on the manner in which intangible cultural heritage is preserved and promoted through community participation and media representation.